2018
DOI: 10.1073/pnas.1804548115
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric plasmonic imaging and detection of single exosomes

Abstract: Exosomes play an important role in numerous cellular processes. Fundamental study and practical use of exosomes are significantly constrained by the lack of analytical tools capable of physical and biochemical characterization. In this paper, we present an optical approach capable of imaging single exosomes in a label-free manner, using interferometric plasmonic microscopy. We demonstrate monitoring of the real-time adsorption of exosomes onto a chemically modified Au surface, calculating the image intensity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
185
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(187 citation statements)
references
References 32 publications
1
185
0
1
Order By: Relevance
“…[17] In this way,s ingle exosomes have been visualized and analyzed after image reconstruction. [18] Alternatively,ahigh-spatial-resolution SPR image has been achieved by multidirectional or azimuthal rotation illumination, resulting in an order of magnitude enhancement in resolution compared to that of conventional SPRM. [19] In addition to the lateral (xy-direction) imaging capability, the SPR imaging technique is ultrasensitive in the vertical direction (z-direction).…”
Section: Spatial and Temporal Resolution Selectivitya Nd Detectionmentioning
confidence: 99%
“…[17] In this way,s ingle exosomes have been visualized and analyzed after image reconstruction. [18] Alternatively,ahigh-spatial-resolution SPR image has been achieved by multidirectional or azimuthal rotation illumination, resulting in an order of magnitude enhancement in resolution compared to that of conventional SPRM. [19] In addition to the lateral (xy-direction) imaging capability, the SPR imaging technique is ultrasensitive in the vertical direction (z-direction).…”
Section: Spatial and Temporal Resolution Selectivitya Nd Detectionmentioning
confidence: 99%
“…This difference could be described as phase, [15] which has not previously been used to describe parabolic patterns.T oq uantify the relationship between the refractive index and the phase of the pattern, ap articlescattering model with ap hase parameter was used. The surface plasmon interferometric scattering field (E s )w as given by: [16]…”
mentioning
confidence: 99%
“…The success of these measurements showed that sensitive optical detection of nano-objects would indeed be possible through non-fluorescent means. In the decade that followed right up to the present day we see a broad array of research efforts, drawn from numerous communities, exploring interferometric detection of single nano-objects such as viruses, DNA, microtubules, exosomes, and proteins [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91]. Interestingly, interferometric microscopies are also flourishing in the general context of label-free imaging of cells and membranes even if nanoparticles are not at the center of attention [75,76,90,[92][93][94][95][96][97][98][99][100][101][102][103][104][105][106].…”
Section: Historical Perspectivementioning
confidence: 99%
“…Interestingly, interferometric microscopies are also flourishing in the general context of label-free imaging of cells and membranes even if nanoparticles are not at the center of attention [75,76,90,[92][93][94][95][96][97][98][99][100][101][102][103][104][105][106]. The underlying physics of these methods remains the same although a plethora of acronyms such as interference reflectance imaging sensing (IRIS) [77], rotating coherent scattering (ROCS) [98], interference plasmonic imaging (iPM) [88], coherent bright-field imaging (COBRI) [107], stroboscopic interference scattering imaging (stroboSCAT) [108], interferometric scattering mass spectrometry (iSCAMS) [109] are on the rise. In what follows, we bring all these techniques under the umbrella of iSCAT, emphasizing the two central concepts and mechanisms of interference and scattering as the basis for recording the extinction signal (nano-shadow) generated by nanoparticles.…”
Section: Historical Perspectivementioning
confidence: 99%